Hot Wheels And Tiktok Live Strategy: When Interactions Drive Unplanned Purchases - Permana, Treeas Khalis; Setyaning, Alldila Nadhira Ayu (UNIVED Press, 2026)
This study aims to analyze how social presence in e-commerce live streaming sessions affects consumers' impulse purchase behavior, specifically on Hot Wheels products. The approach used is Stimulus-Organism-Response (SOR), focusing on three social stimuli-broadcasters, other viewers, and platforms-and two emotional responses, namely arousal and pleasure. Data were collected through a survey of 202 respondents who have participated in TikTok live streaming and are active buyers of Hot Wheels products. The analysis technique used Partial Least Squares Structural Equation Modeling (PLS-SEM). The results showed that social presence significantly influenced consumers' emotional state, which then had a positive impact on impulse purchases. This study contributes to the digital marketing literature and offers practical insights for businesses in designing more effective live streaming strategies.